Novel AAV variants with improved tropism for human Schwann cells - Matthieu Drouyer; Tak-Ho Chu; Elodie Labit; Florencia Haase; Renina Gale Navarro; Deborah Nazareth; Nicole Rosin; Jessica Merjane; Suzanne Scott; Marti Cabanes-Creus; Adrian Westhaus; Erhua Zhu; et al. (Molecular Therapy: Methods & Clinical Development, 2024)
Gene therapies and associated technologies are transforming biomedical research and enabling novel therapeutic options for patients living with debilitating and incurable genetic disorders. The vector system based on recombinant adeno-associated viral vectors (AAVs) has shown great promise in recent clinical trials for genetic diseases of multiple organs, such as the liver and the nervous system. Despite recent successes toward the development of novel bioengineered AAV variants for improved transduction of primary human tissues and cells, vectors that can efficiently transduce human Schwann cells (hSCs) have yet to be identified. Here, we report the application of the functional transduction-RNA selection method in primary hSCs for the development of AAV variants for specific and efficient transgene delivery to hSCs. The two identified capsid variants, Pep2hSC1 and Pep2hSC2, show conserved potency for delivery across various in vitro, in vivo, and ex vivo models of hSCs. These novel AAV capsids will serve as valuable research tools, forming the basis for therapeutic solutions for both SC-related disorders or peripheral nervous system injury.